2007
DOI: 10.1590/s0100-879x2007000100007
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E polymorphism in Brazilian dyslipidemic individuals: Ouro Preto study

Abstract: The influence of apolipoprotein E alleles and genotypes on plasma lipid levels was determined in 185 individuals of mixed ethnicity living in Ouro Preto, Brazil. DNA was obtained from blood samples and the genotypes were determined by an RFLP-PCR procedure. The *3 allele was the most frequent (72%), followed by *4 (20%) and *2 (8%); *4 frequency was higher and *2 frequency was lower in the dyslipidemic group than in the normal control group. The *2 carriers presented lower LDL and total cholesterol levels comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 24 publications
(23 reference statements)
5
19
2
2
Order By: Relevance
“…Mendes-Lana A demonstrated that the presence of Apo E2 can confer a protective effect, the presence of Apo E4 implies an enhanced risk of dyslipidemia [26], and our results are in accordance with above studies for E 4 allele. The study confirms the significant association between ApoE4 allele and hyperlipidemia.…”
Section: Discussionsupporting
confidence: 92%
“…Mendes-Lana A demonstrated that the presence of Apo E2 can confer a protective effect, the presence of Apo E4 implies an enhanced risk of dyslipidemia [26], and our results are in accordance with above studies for E 4 allele. The study confirms the significant association between ApoE4 allele and hyperlipidemia.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the frequency of the allele was lower than the one observed in northern European countries, such as Ireland (22%) 28 and lower than the one found in the town of Ouro Preto, state of Minas Gerais, Brazil (20%) 29 , where the African contribution for the formation of the population was higher.…”
Section: Discussioncontrasting
confidence: 59%
“…The occurrence of dyslipidemia was higher among adults bearing allele 4 [29]. Additionally, another study in this population showed that lipoprotein (a) serum levels were highly correlated with the occurrence of ischaemic heart disease and the Framingham risk score [6].…”
Section: Introductionmentioning
confidence: 61%